Readiness and Influencing Factors for Disruptive Technologies Application in Malaysian Highway Maintenance: A Qualitative Study - Zul Zakiyuddin Ahmad Rashid (International Journal of Integrated Engineering, 2025)
The Fourth Industrial Revolution (IR 4.0) is transforming the construction industry through digitalisation and automation, offering opportunities for cost reduction and improved efficiency in infrastructure projects. This study investigates the readiness of Malaysian highway operators to adopt disruptive technologies during the operation and maintenance phases, identifying key influencing factors. A qualitative approach was employed, with semi-structured interviews conducted between June 2023 and March 2024 involving five experienced professionals from various highway concessionaires. Data analysis using NVivo 14 revealed that although operators show readiness for certain technologies, adoption levels vary across maintenance processes. Thematic analysis identified four critical factors influencing implementation: Discomfort, Innovativeness, Insecurity, and Optimism. The findings suggest that Innovativeness and Optimism drive adoption by potentially reducing labour dependency while enhancing efficiency and safety. In contrast, addressing Discomfort and Insecurity could lead to long-term time and cost savings. The study concludes that overcoming these barriers may accelerate technology integration in highway maintenance. Future research should examine emerging technologies such as machine learning, blockchain, and big data analytics to further enhance highway infrastructure management. This research contributes to a deeper understanding of the human factors influencing technology adoption in transportation infrastructure maintenance.